Bone marrow niches in haematological malignancies - Méndez-Ferrer, Simón; Bonnet, Dominique; Steensma, David P.; Hasserjian, Robert P.; Ghobrial, Irene M.; Gribben, John G.; Andreeff , Michael; Krause, Daniela S. (Nature reviews. Cancer, 2020)
Haematological malignancies were previously thought to be driven solely by genetic or epigenetic lesions within haematopoietic cells. However, the niches that maintain and regulate daily production of blood and immune cells are now increasingly being recognized as having an important role in the pathogenesis and chemoresistance of haematological malignancies. Within haematopoietic cells, the accumulation of a small number of recurrent mutations initiates malignancy. Concomitantly, specific alterations of the niches, which support haematopoietic stem cells and their progeny, can act as predisposition events, facilitating mutant haematopoietic cell survival and expansion as well as contributing to malignancy progression and providing protection of malignant cells from chemotherapy, ultimately leading to relapse. In this Perspective, we summarize our current understanding of the composition and function of the specialized haematopoietic niches of the bone marrow during health and disease. We discuss disease mechanisms (rather than malignancy subtypes) to provide a comprehensive description of key niche-associated pathways that are shared across multiple haematological malignancies. These mechanisms include primary driver mutations in bone marrow niche cells, changes associated with increased hypoxia, angiogenesis and inflammation as well as metabolic reprogramming by stromal niche cells. Consequently, remodelling of bone marrow niches can facilitate immune evasion and activation of survival pathways favouring malignant haematopoietic cell maintenance, defence against excessive reactive oxygen species and protection from chemotherapy. Lastly, we suggest guidelines for the handling and biobanking of patient samples and analysis of the niche to ensure that basic research identifying therapeutic targets can be more efficiently translated to the clinic. The hope is that integrating knowledge of how bone marrow niches contribute to haematological disease predisposition, initiation, progression and response to therapy into future clinical practice will likely improve the treatment of these disorders. This Perspective outlines our current understanding of how the bone marrow niche contributes to both the initiation and the progression of haematological malignancies and suggests guidelines for the field which might help to overcome existing research challenges.